Activating the role of local communities in the framework of the partnership for sustainable local development - a policy clusters in the French experience as a model - العابد, لزهر; دهان, محمد (Finance and Business Economies Review, 2019)
The study aims at clarifying how to activate the role of local communities in achieving sustainable local development through the partnership mechanism, by presenting the experience of cluster policy in France as a model, The study concluded that local communities form a partnership between them and the publicprivate partnership to carry out development projects. The study also found that the intervention of local communities as an active partner for achieving sustainable local development through contributing to the creation of clusters is a member of the board of directors. It also contributes to financing and educating various stakeholders about the importance of establishing partnership agreements to achieve research projects of a sustainable nature.